Effect of South Asian Free Trade Area agreement on trade and macroeconomics of the region - Peiris, Thelge Ushan Indika (2019)
This study investigates the desirability of South Asian Free Trade Area (SAFTA) in attaining static and dynamic efficiencies of trade integration, and in turn, its effect on economic growth of the region. The static efficiency of SAFTA is measured through its potentiality in trade creation and trade diversion. The dynamic time path of static efficiency is also investigated to measure the timely realizations of trade creation and trade diversion. The static analysis of SAFTA is further extended to measure the effect of political factors, because prevailing political tension within the region is appeared to be the main hindrance in expanding trade. In measuring its dynamic efficiency, the potential of SAFTA in improving macroeconomic factors of the region is measured. Six (6) theoretically chosen macroeconomic variables (Macroeconomic Policy Credibility, Price Distortion, Physical Investment, Inward FDI, Technology Transfer, and Human Capital) are considered on this regard. Finally, macroeconomic channels that mediate static efficiency of SAFTA in boosting economic growth are investigated to measure the growth effects of SAFTA. The desirability of SAFTA is measured over the period 2003 to 2013 considering only seven (07) South Asian countries (Afghanistan, Bangladesh, India, Maldives, Nepal, Pakistan, and Sri Lanka). Bhutan is not taken to the sample due to data constraint. When measuring trade creation and trade diversion effects, a gravity model is augmented to represent both static and dynamic model specifications separately. Static gravity models are measured using linear panel regression models, while two-step GMM and two-step system GMM models are used for the dynamic gravity models. When estimating these models, regions bilateral trade with 87 trading partners is used. To measure the dynamic efficiency, linear panel regression models and two-stage least-squares generalized panel data models are used depending on the model specifications of the macroeconomic variables. When estimating the growth effects of SAFTA, macroeconomic variables used to measure the dynamic efficiency are taken as mediator variables. Thus, a structural model with seven simultaneous equations, each for the six mediator variables and one for the economic growth, are used to measure the mediation effect of SAFTA in boosting economic growth of the region. The estimated results for both static and dynamic gravity models confirm the presence of significant intra-bloc and extra-bloc trade expansions following SAFTA. When moving from static to dynamic gravity models a significant trade persistency is reported, however, trade expansions significantly reduced. Also, results further confirm the presence of significant anticipation effects for SAFTA. Meanwhile, this study empirically confirms the existence of weaker governance and inefficient institutions within South Asian political environment that hinder region’s trade. The dynamic efficiency of SAFTA is also supported by the results. That is, with the exception of human capital equation all the other macroeconomic equations depict a statistically significant coefficient for SAFTA with the expected signs. Finally, results for the growth effects indicate that SAFTA positively and significantly influences economic growth through two out of six channels: macroeconomic policy credibility and physical investment. This indicates that SAFTA carries its economic growth effects to the region mainly through its potential in stabilizing region’s macroeconomic policies and encouraging physical investment. Therefore, with the presence of static and dynamic efficiencies, and significant economic growth effects, it is recommended to bring SAFTA to its full potential by further reducing tariffs and removing other trade barriers.